3-D CFD Modeling of a Slanted Receiver in a Compact Linear Fresnel Plant with Etendue-Matched Mirror Field. (May 2015) - Rungasamy, A.E.; Craig, K.J.; Meyer, J.P.
Abstract: Compact linear Fresnel receivers can be modified to include an etendue conserving mirror field as opposed to a flat field. Etendue can be used as an indicator of the losses within the system and therefore the optical optimization of the mirror field seeks to conserve incoming etendue. This can be done once for peak conditions and subsequently fixed with mirrors rotating throughout the day; or the mirror axis points can also be allowed to move up and down throughout the day, creating new etendue conservation curves. Radiation is modeled using discrete ordinates with no conduction in a two-dimensional and the absorbed radiation flux profiles are subsequently patched onto a three-dimensional slanted receiver as a heat source. The commercial software package ANSYS Fluent v15.0 was used together with the Matlab toolset to study the influence of different mirror fields on the amount of radiation transferred to the collector pipes.